Alpha‐klotho and peritoneal membrane status: A hypothesis generating study. (1st December 2022) - Branco, Patrícia; Martins, Ana Rita; Calça, Rita; Mateus, Catarina; Jervis, Maria João; Rodrigues, Anabela; Lopes, Sofia Azeredo; Civantos, Ester; Mas‐Fontao, Sebastian; Gaspar, Augusta; Ramos, Sância; Morello, Judit; et al.
Abstract: Background: Long‐term success of peritoneal dialysis relies on the integrity of the peritoneal membrane. This proof‐of‐concept study addressed the hypothesis that fibrosis is already present in the membrane at pre‐dialysis and that the membrane status is related to the individual's uraemic fingerprint. Methods: A clinical‐mechanistic, transversal, single‐centre study was conducted. Pre‐dialysis peritoneal biopsies were scored considering the submesothelial compact zone thickness (STM), vasculopathy and inflammation. We investigated if the membrane status could be inferred from a panel of proteins (α‐Klotho, Galectin‐3, FGF21, FGF23, Tweak, TNFα and hsPCR) in blood. Results: A total 58 incident patients aged 56 ± 15 years old were included, 31% female, 55% hypertension, 29% diabetic and 24% obese. Person‐to‐person STM was found to be highly variable and 38% of patients were fibrosis positive. Both α‐Klotho ( Spearman r  = −.7491, p  < 0.001) and FGF21 ( Spearman r  = −.5102, p  < 0.001) were negatively associated with STM. α‐Klotho, but not FGF21, was able to discriminate fibrosis from nonfibrosis with/without inflammation and vasculopathy. PLS models identified α‐Klotho as the protein most relevant for fibrosis. α‐Klotho was independently associated with fibrosis of the peritoneal membrane (OR = .991 (.896–.997), p  = 0.002). Conclusion: Before the start of dialysis in incident patients, some patients already present fibrosis of the peritoneal membrane and other patients do not. Our findings suggest that α‐Klotho may be implicated in fibrosis of the peritoneal membrane. Abstract : We have been interested in contributing to long‐term success of peritoneal dialysis, which relies on the integrity of the peritoneal membrane. In this proof‐of‐concept, mechanistic, clinical study we addressed the hypothesis that fibrosis is already present in the membrane at pre‐dialysis and that the membrane status is related to the individual's uremic fingerprint. To address this hypothesis, we scored pre‐dialysis peritoneal biopsies for fibrosis, vasculopathy and inflammation and we investigate if fibrosis could be inferred from circulating uremic toxins. We discover that α‐Klotho was able to discriminate fibrosis from non‐fibrosis peritoneal membranes. Our paper brings novelty for the peritoneal dialysis field and suggest that this aging related molecule, even in young patients, may be implicated in fibrosis of the peritoneal membrane.